The Role of Water and its Impact on Urban Spaces in Cities - بيازيد خالد (Latakia University Journal -Engineering Sciences Series, 2021)
Water has had an important role since ancient times in human life, and they have woven stories, myths and epics around it since the beginning of creation. Diseases. The use of water in its various formations is one of the most important elements of landscape architecture in cities, as it gives it distinct aesthetic, cultural and environmental values ​​that help the city dweller to overcome the many problems and crises that cities suffer today from congestion, noise and pollution, which negatively affect the physical and psychological health of their inhabitants. Man has tried to return to nature by simulating the forms of water in it from waterfalls, rivers and lakes and its various uses, especially in heritage architecture. The research focused on shedding light on some of the modern uses of water and its practical, aesthetic and environmental benefits, and concluded with a set of findings and recommendations that enhance this use in our contemporary life, which means reaching healthy and viable cities.